Tumor characteristics and survival rate of axillary metastatic breast cancer patients: a three decades retrospective cohort study - Seyed Mohamad Sadegh Mousavi-kiasary; Mahdis Bayat; Fereshteh Abbasvandi; Batoul Khoundabi; Fatemeh Mousavi; Atieh Akbari; Maryam Bagherian; Afsoon Zandi; Behnam Honarvar; Mohammad Esmaeil Akbari (Scientific Reports, 2025)
Abstract Background: Lymph node (LN) involvement, as an important prognostic factor in breast cancer (BC) patients, has a crucial role in their therapeutic approach. Consequently, a great desire is to thoroughly assess the patients based on their axillary LN status. The present study evaluated the characteristics and survival rate of axillary metastatic BC patients in a Tertiary and referral center. Method: The overall survival, disease-free survival, and clinicopathological characteristics of axillary metastatic BC patients referred to the Cancer Research Center in Tehran, Iran, from 1991 to 2022 were assessed retrospectively. We obtained patients’ clinical data from prospectively maintained registries. Result: Among the total 3399 recruited patients, 49.1%, 26.3%,13.1%, and 6.4% were pN0, pN1, pN2 and pN3, respectively. The pN0 group patients showed a significantly lower Hazard Ratio (HR) for DFS and OS compared to others. Moreover, estrogen and progesterone receptors, human epidermal growth factor2, tumor pathology type and tumor grade were prognostic factors of axillary LN status. Accordingly, pN0 patients had a lower recurrence risk than the others (P = 0.01). Conclusion: The axillary lymph node status has been considered as one of the fundamental factors determining the therapeutic strategy and prognosis of BC patients, which has an association with tumor characteristics. Regarding the crucial impact of the LN status on the survival landscape of breast cancer patients, accurate detection of the involved one and close screening follow-up of patients with more metastatic LNs during the surgery have a high value.